DataScribe: user manual - Aubert, C.; Devare, Medha (International Institute of Tropical Agriculture, 2023)
Build surveys and data collection forms in ODK format with data variables that comply with community standards for data that is Findable, Accessible, Interoperable and Reusable (FAIR) from the collection point.